Adam Watkins' 4th Birthday Party In Backyard With Friends - Watkins, Howard::::::::: (1982)
Annie Tilley painting red heart on cheek of Rose Watkins Albert Watkins wearing his Cherokee Indian headdress; Cerveza BUD neon sign in garage window